Impact of postoperative macular comorbidity on visual outcomes after Descemet’s membrane endothelial keratoplasty: A multicenter analysis - Naoya Nakagawa; Ami Igarashi; Hideaki Yokogawa; Akira Kobayashi; Tomomi Higashide; Satoru Yamagami; Takahiko Hayashi (PLoS ONE, 2026)
The aim of this study was to identify the clinical factors associated with postoperative visual acuity following Descemet’s membrane endothelial keratoplasty (DMEK), with emphasis on the impact of macular diseases. This retrospective multicenter study included consecutive eyes that underwent DMEK between March 1, 2011, and June 30, 2022, and had available optical coherence tomography findings. Eyes with other ocular diseases causing visual loss were excluded. Overall, 77 eyes of 66 patients were included in the study. Univariable and multivariable regression analyses were performed to identify the predictors of best-corrected visual acuity (BCVA) at the final follow-up. Worse preoperative visual acuity and macular comorbidity were identified as independent predictors of poorer postoperative BCVA. Among macular pathologies, cystoid macular edema was most strongly correlated with reduced vision in the univariable analysis (β = 0.195; p = 0.016). In the subgroup analysis, worse preoperative visual acuity and macular comorbidity remained significant predictors (p < 0.001 and p = 0.023, respectively). Other comorbidities such as epiretinal membrane and wet age-related macular degeneration were not significant predictors. Worse preoperative visual acuity and macular comorbidity are independent risk factors for suboptimal visual recovery after DMEK. These findings highlight the importance of comprehensive preoperative retinal assessment and individualized postoperative management to optimize visual outcomes.